INCOME ANALYSIS OF BUSINESS REVENUE IN KENDARI CITY (Revenue analysis of Meatballs in Kendari) - Gustina, Gustina; Hafid, Harapin; Aka, Rahim (Pascasarjana Universitas Sulawesi Tenggara, 2020)
This research is supposed to know meatballs seller income in Kendari City and to analyze the balance of the income of cost. This research held from May until June 2013 in Kendari City Southeast Province. This research is applying with the survey method and determination location with purposive sampling. The research location consists of Mandongga District, Kadia District, Baruga District, and West Kendari Discrete. The respondent's determination is using census method meatball sellers as a respondent is a seller only sell the meatball without the other type of it. The total of respondents is 13 people. Data that wed to research is classified include two types are primer data and secondary data. Data analyze is used to count the income π = TR-TC meanwhile to count the balance of cost income is R/C ratio = income totally and outcome the result of the research shows us that average of outcome still issued by meatball sellers Kendari City Rp 1.780.564,00/mouth/ seller, variable cost is 9.040.584,00 /mouth/seller and the total cost is 10.821.130,00 mouth/seller. On the other hand, the seller income is 13.594.000,00/mouth/seller, income is 2.789.500/mouth/seller and the balance of the income of cost is 1,2 it means that the seller meatballs business in Kendari city is suitable to develop.